Hole of hydrogen peroxide on the interaction of [Vigna unguiculata (L.) Walp] with the fungus Colletotrichum gloesporioides (Penz.) Penz. & Sacc. [Teleomorpho Glomerella cingulata (Stonem.) Spauld. & Von Schrenk] - Ygor Raphael Gomes Eloy (2007)
Cowpea is an important legume of the Northeast of Brazil and its yield is affected by Colletotrichum fungi. These fungi are known to occur on and cause disease anthracnose on the broad range of plants. In addition, the rapid and transient accumulation of reactive oxygen species, termed âoxidative burstâ, is one of the earliest observable reaction of plant cells to microbial infection. As plant H2O2 is believed to have direct antimicrobial effects on pathogens it was raised the hypothesis that alteration of H2O2 concentrations by pharmacological compounds could confer differences in susceptibility of the cowpea genotype BR-3-Tracuateua to C. gloeosporioides attack. Thus, seeds were germinated on humid GermitestÂ paper and after four days seedlings were transferred to hydroponic solution. Eight days later, the primary leaves were excised, infiltrated with glucose oxidase (GO+G), salicylic acid (AS), catalase (CAT) and diphenyleneiodonium chloride (DPI) transferred to Petri dishes and inoculated with 2.0 x 105 spores mL-1 fungal suspension on the adaxial surface. After, leaves were placed in darkness and collected at 12, 24, 48 and 72 hours. By GO+G and SA leaf treatments showed 144.96 and 186.05 nmol H2O2 g-1 fresh mass (FM), respectively, and the fungus presented a subcuticular, intramural necrotrophic strategy, forming secondary hyphae associated with a quick spread and a rapid killing of the host cells. On the leaves treated with SA, it was observed lipid peroxidation and the absence of melanized appresoria. However, CAT and DPI treatment leaves presented 55.50 nmol H2O2 g-1 FM and the fungus showed hemibiotrophic infection-type, with globular vesicles and primary and secondary hyphae formation. All results suggest that despite H2O2 influenced directly the fungal infection process-type it does not confer resistance of cowpea to C. gloeosporioides.